2016
DOI: 10.1038/srep37398
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Spin-Current Operation in a Cu Nano-Ring

Abstract: An all-metal lateral spin-valve structure has been fabricated with a medial Copper nano-ring to split the diffusive spin-current path. We have demonstrated significant modulation of the non-local signal by the application of a magnetic field gradient across the nano-ring, which is up to 30% more efficient than the conventional Hanle configuration at room temperature. This was achieved by passing a dc current through a current-carrying bar to provide a locally induced Ampère field. We have shown that in this ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, the small differential signals compared with the measurement errors rule out a conclusive observation of the effect at this stage. As can be seen from the large modulation efficiency of the Ampère-fieldgenerating current-gating of a nanometric nano-ring [28], the miniaturisation of our devices is expected to increase our modulation efficiency. The optical gating technique in our structure could have a significant advantage over conventional electric-field gating due to a lower power consumption up to 25% [29].…”
Section: Resultsmentioning
confidence: 99%
“…However, the small differential signals compared with the measurement errors rule out a conclusive observation of the effect at this stage. As can be seen from the large modulation efficiency of the Ampère-fieldgenerating current-gating of a nanometric nano-ring [28], the miniaturisation of our devices is expected to increase our modulation efficiency. The optical gating technique in our structure could have a significant advantage over conventional electric-field gating due to a lower power consumption up to 25% [29].…”
Section: Resultsmentioning
confidence: 99%
“…This stimulated the researchers' interest on spin injection in lateral spin valves. [8][9][10] So far, spin polarized current has been injected into various kinds of materials, such as copper, [11] silver, [12][13][14] gold, [15,16] magnesium, [17] and two dimensional materials. [18][19][20] It is found that the magnitude of the spin accumulation signal is quite small when the ferromagnetic material is directly attached to the non-ferromagnetic materials.…”
Section: Introductionmentioning
confidence: 99%